The Folklorist Pedro Echevarría Bravo (1905-1990), his Galician Period and the “Folkloric Missions” (1951-1960): Collecting Galician Traditional Music in the 1950s - Puentes-Blanco, Andrea (Madrygal. Revista de Estudios Gallegos, 2024)
Pedro Echevarría Bravo (1905-1990) was a prominent Spanish musicologist and folklorist of the twentieth century. Yet, despite the significance of his work, studies devoted to his career and contributions remain scarce, and his name is absent from the major reference works on music. After a long career as a band director and an intensive period of folk‑song collecting in Castilla‑La Mancha, Echevarría moved to Galicia in 1953, where he continued his professional activity until around 1965. During these years he directed the municipal band of A Coruña (1953-1954) and, subsequently, the Compostela band (1954-1965). This Galician chapter of his career –and particularly his research on and collection of Galician folklore– has received almost no scholarly attention. Between 1951 and 1960, Echevarría gathered hundreds of traditional songs across Galicia. His work was supported by the Folklore Section of the former Spanish Institute of Musicology, as part of the pioneering nationwide project to document and study traditional music that ran between 1944 and 1960, known as the “Folkloric Missions”. Echevarría had already participated in this project during his years in La Mancha, and he went on to carry out eight such missions in Galicia. Today, the results of that work can be consulted through the open‑access digital platform Fondo de Música Tradicional IMF‑CSIC. Drawing on a wide range of documentary sources, this article reconstructs Echevarría’s presence in Galicia during the 1950s and 1960s, and situates his folkloric research within the broader context of twentieth‑century efforts to preserve and study Galician oral music traditions.
Keywords: Pedro Echevarría Bravo; Galicia; Music of Oral Tradition; “Misiones Folklóricas”; Fondo de Música Tradicional IMF-CSIC